PENGALAMAN IBU MULTIGRAVIDA BERSALIN DENGAN METODE GENTLE BIRTH DI KLINIK BUMI SEHAT KABUPATEN GIANYAR - Kadek Widiantari; Ni Made Dewianti (JOMIS (Journal of Midwifery Science), 2021)
ASTRACT Increased choice with the method of sectio caesarea surgery throughout the world was highlighted and become the public health problems. One of the methods used by Midwifery Practitioners in reducing the incidence of sectio caesarea is by applying the gentle birth. Gentle birth is a method of labor that is made as comfortable as possible and has minimal trauma. This study aims to find out the experience of gentle birth on multigravida woman at Bumi Sehat Clinic in Gianyar Regency. This study used a qualitative design with a transcendental phenomenology approach. The sample selection in this study used a purposive sampling technique with the number of informants as many as 10 people and one key informant namely the Coordinating Midwife from Bumi Sehat Clinic. Interviews were conducted in each participant's residence and key informant's workplace using in-depth interview guidelines. The results of the interviews were analyzed using thematic analysis. The results of the study found two major themes that were; 1) the reason multigravida woman chose to give birth with a gentle birth method consisting of knowledge, perceptions, psychological aspects, maternal experiences without gentle birth methods, health facilities, sources of information and husband support, 2) feeling after giving birth with gentle birth method. Efforts that can be made in increasing labor with the gentle birth method is by organizing socialization especially for pregnant women about the benefits of gentle birth method, conducting training for health workers on the implementation of gentle birth.